The Colony of Delaware - Whitehurst, Susan (New York The Rosen Publishing Group,Inc, 2000)
An introduction to the lives of the early settlers in the Delaware colony, from the early attempts of the Dutch, Swedes, and English to colonize to Delaware's role in the American Revolution.
Keywords: Delaware -- History -- Colonial period, ca. 1600 - 1775.; Series: The library of the thirteen colonies and the lost colony